2012
DOI: 10.1088/2041-8205/750/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

High-Latitude Solar Torsional Oscillations During Phases of Changing Magnetic Cycle Amplitude

Abstract: Torsional oscillations are variations of the solar differential rotation that are strongly linked to the magnetic cycle of the Sun. Helioseismic inversions have revealed significant differences in the high-latitude branch of torsional oscillations between cycle 23 and cycle 24. Here we employ a non-kinematic flux-transport dynamo model that has been used previously to study torsional oscillations and simulate the response of the high-latitude branch to a change in the amplitude of the magnetic cycle. It is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…In the model of Rempel (2006), the poleward branch arises easily from a flux-transport dynamo calculation, whereas surface thermal effects, as suggested by Spruit (2003), are needed to reproduce the observed low-latitude branch. Rempel (2012) found that if the polar fields weaken-as has indeed been observed in recent years (Hoeksema 2009)-the overall rotation at high latitudes slows down, masking the appearance of the poleward branch when the rotation-rate residuals are formed by subtracting a long-term average.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the model of Rempel (2006), the poleward branch arises easily from a flux-transport dynamo calculation, whereas surface thermal effects, as suggested by Spruit (2003), are needed to reproduce the observed low-latitude branch. Rempel (2012) found that if the polar fields weaken-as has indeed been observed in recent years (Hoeksema 2009)-the overall rotation at high latitudes slows down, masking the appearance of the poleward branch when the rotation-rate residuals are formed by subtracting a long-term average.…”
Section: Introductionmentioning
confidence: 65%
“…A less drastic possible explanation for the non-appearance of the new poleward branch has been put forward by Rempel (2012). In the model of Rempel (2006), the poleward branch arises easily from a flux-transport dynamo calculation, whereas surface thermal effects, as suggested by Spruit (2003), are needed to reproduce the observed low-latitude branch.…”
Section: Introductionmentioning
confidence: 99%
“…Howe et al (2013) have combined results from all these three instruments to find changes in the high-latitude branch of the torsional oscillations from one solar cycle to the next, as modeled by Rempel (2012). A confirmation of such variations by SO/PHI would definitively settle their existence, which has consequences for the rotation pattern at high latitudes.…”
Section: Science Goalsmentioning
confidence: 99%
“…During the extended minimum following Cycle 23, the new equatorward branch was visible as expected, but it moved more slowly during the declining phase of Cycle 23 than the corresponding feature in the previous cycle (Howe et al 2009), resulting in an effective length of about 12.3 years for Cycle 23. During Cycle 24, the poleward branch was unusually weak, and indeed it is hardly visible in a conventional torsional-oscillation plot such as that in Figure 1 because it is superimposed on a slower overall rotation at high latitude (Howe et al 2013), which may be related to the weaker polar fields in Cycle 24 (Rempel 2012).…”
Section: Introductionmentioning
confidence: 97%